Joint implementation: a promising instrument for climate protection - Axel Michaelowa (Intereconomics, 1995)
The first Conference of the Parties to the UN Framework Convention on Climate Change opened the path for a new policy instrument to mitigate anthropogenic climate change. It instituted a pilot phase for international emission offsets, “Joint Implementation”, open for all signatories to the Convention. During the pilot phase, however, emission reductions achieved abroad cannot be credited to domestic emission targets. By 2000, a decision on crediting and the final structure of the Joint Implementation regime must be taken by the Conference of the Parties.
Keywords: 330; Environment